CYP2D7––2D6 hybrid tandems: identification of novel CYP2D6 duplication arrangements and implications for phenotype prediction. (January 2010) - Gaedigk, Andrea; Fuhr, Uwe; Johnson, Charlene; Béérard, Anick; Bradford, L DiAnne; Leeder, J Steven
Aims: Allelic variants of cytochrome P450 CYP2D6 ( CYP2D6 ), such as gene deletion, duplication, multiplication and conversion, contribute to the wide range of CYP2D6 activity. Novel gene arrangements were discovered and characterized.Materials & methods: DNA from 32 Caucasian and 59 African––American duplication-positive subjects were analyzed by long-range PCR and genotyping to detect CYP2D7––2D6 hybrid tandem alleles. Novel allelic variants were sequenced and a strategy for the detection and analysis of hybrid genes was refined.Results: CYP2D7––2D6 hybrid tandem alleles were identified in one African––American and four Caucasian subjects. Three novel hybrid genes were found on CYP2D6*1 and CYP2D6*2 duplication backgrounds and designated CYP2D6*76, *77 and *78 . CYP2D7 to 2D6 conversion occurred in introns 1 and 4, and exon 9. All carried a T-insertion in exon 1 abolishing activity. In Caucasians, four out of 33 (12%) of the duplication-positive alleles were hybrid tandems, three CYP2D6*77 + *2 and one CYP2D6*78 + *2 . By contrast, in African––Americans only one of 60 duplication-positive alleles was identified as a hybrid tandem. This allele was designated CYP2D6*76 + *1 .Conclusion: Hybrid tandem alleles occur infrequently (<0.25%) in Caucasians, but may explain why not every subject with a CYP2D6 duplication presents with an ultrarapid metabolizer phenotype.